¿Evidencia versus Forma? Evidencia como consejera de Forma para optimizar el consumo energético residencial (ARQUISUR Revista, 2014)
Working on the margins of the discipline, traditionally untouchable, constitutes a substantial challenge for contemporary professional practice, as technological innovations can produce significant changes and benefits government founded social housing constitutes a relevant object to explore and explode, incorporating new methods of analysis rendered possible by new information and knowledge management digital technologies. Therefore, it is possible to produce an expanded field of knowledge, analyzing each case and bringing into play a large number of variables in order to offer socially responsible alternative.